Molecular analysis of Peganum harmala L. callus to determine the gene expression of beta-carboline alkaloids harmine and harmaline - Mutasher, H. H.; Attiya, H. J. (Iraqi Journal of Science, 2019)
The external signals are used as elicitors that can modify the levels of secondary metabolites production and trigger the biotechnological enforcements to improve plant production. In this study, sodium chloride NaCl was used as a stimulating factor for the production of beta-carboline alkaloids, harmine and harmaline, in Peganum harmala. The in vitro induced callus of P. harmalain was used as a source for alkaloid production in the stimulating experiments with sodium chloride. The results illustrated that 2 mg.l-1 of NaCl increased the fresh and dry weight of callus with an average of 944.30 and 72.0 mg, respectively. In a comparative analysis through Gas Chromatography (GC), high concentrations of harmine of 58.55 µg.g-1 from the root and 56.50µg.g-1 from stem callus were recorded upon treatment with 4 mg.l-1 of NaCl. Treatment with 4 mg.l-1 NaCl also showed an increased amount of harmaline concentration in both root and stem, with values of 2.72 and 2.65 µg.g-1, respectively. The analysis and calculation of gene expression by real-time PCR of RNA showed that the induced stem callus had a high gene expression with a copy number of 229,030. While in the root, the effect of higher salinity increased the percentage of alkaloids without increasing the copy number of gene expression.